Distinct Cutoff Values of Adalimumab Trough Levels Are Associated With Different Therapeutic Outcomes in Patients With Inflammatory Bowel Disease. Issue 3 (27th November 2019) - Park, Sang Hyoung; Al-Bawardy, Badr; Aniwan, Satimai; Kane, Sunanda V; Coelho-Prabhu, Nayantara; Papadakis, Konstantinos A; Kisiel, John B; Bruining, David H; Faubion, William A; Raffals, Laura E; Pardi, Darrell S; Tremaine, William J; et al.
Abstract: Background and Aims: We aimed to evaluate the relationship of serum adalimumab trough levels (ATL) with disease activity of inflammatory bowel disease (IBD) patients in a large, well-characterized referral center-based cohort. Methods: We compared serum ATL between those with clinical, biochemical, or endoscopic/radiologic disease activity and those without. Results: A total of 236 patients with IBD were included. Higher cutoff levels were associated with endoscopic and/or radiologic responses (cutoff value: 5.3 mcg/mL, P = 0.003) compared with improvement in C-reactive protein (cutoff value: 4.3 mcg/mL, P = 0.031). Conclusions: Higher cutoff ATL was associated with endoscopic and/or radiologic response. Lay Summary: The drug level of adalimumab in the blood was associated with the clinical outcomes of inflammatory bowel disease. Also, the higher cutoff level of adalimumab was required for more objective outcomes of treatment for inflammatory bowel disease.